Analysis of the Alaska Volcano Observatory's Response Time to Volcanic Explosions-1989 to 2016 - Power, John A.; Cameron, Cheryl E. (Frontiers in Earth Science, 2018)
Abstract A major goal of volcano monitoring is the rapid identification of volcanic explosions and subsequent warning of associated hazards. Between 1988 and 2016 the Alaska Volcano Observatory (AVO) responded to at least 54 separate volcanic eruptions. During this period, AVO’s monitoring program relied principally on seismic and satellite remote sensing data, supplemented with geodetic, gas, and visual observations to track volcanic unrest. In this study we focus on AVO’s response time, or the time required for AVO to (1) identify seismic signals associated with large ash-producing volcanic explosions and (2) initiate public warnings. We restrict this analysis to volcanoes monitored by a local seismic network and explosive in character. We focus on the 1989-90 eruption of Redoubt Volcano (VEI 3), the 1992 eruption of Mount Spurr (VEI 4), the 1999 eruption of Shishaldin Volcano (VEI 3), the 2006 eruption of Augustine Volcano (VEI 3) and the 2016 eruption of Pavlof Volcano (VEI 2) as detailed records of the timing of formal warnings are preserved. These eruption sequences allow us to evaluate AVO’s response time under a number of monitoring scenarios, including both expected and surprise eruptions as well as individual and repetitive sequences of explosive events. Recorded response time ranges from ~1 to 86 minutes. The shorter response times (~1 to 13 minutes) were achieved during sequences of explosive events at Redoubt (1989-90), Spurr (1992) and Augustine (2006). The longer response times (31 to 86 minutes) are recorded for unexpected or surprise explosions such as Spurr (August 18, 1992) and Pavlof (2016) and the only or first explosions in an eruptive sequence such as Shishaldin (1999) and Augustine (2006).